Exergy analysis of engines fuelled with biodiesel from high oleic soybeans based on experimental values. (2nd December 2009) - Caliskan, Hakan; Tat, Mustafa Ertunc; Hepbasli, Arif; Van Gerpen, Jon H.
This study dealt with energy and exergy analyses of a John Deere 4045T diesel engine run with no. 2 diesel fuel, Soybean oil Methyl Ester (SME) and High-Oleic soybean oil Methyl Ester (HOME) at 1400 1/min. It was aimed at determining energy and exergy efficiencies, energy losses and exergy destructions of the combustion process and comparing exergetically the fuels used. The specific exergy of the fuels was calculated to be εfuel, No.2 Diesel > εfuel, HOME > εfuel, SME, while energy (thermal) and exergy efficiencies were 40.5% and 37.8%, respectively. There were no statistically significant differences between the fuels based on the Tukey method.